Nasal polyps - Clinical Profile and Management in a Tertiary Care Hospital - FAZAL-I-WAHID SAEED KHAN SHAFIULLAH, MUHAMMAD SALEEM AFRIDI (Journal of Fatima Jinnah Medical University, 2018)
Objective: To evaluate the clinical profile and management of nasal polyposis as seen at a tertiary care hospital. Patients and Methods: A 3-year (2009-2011) prospective study of 63 nasal polyposis patients depicting the clinical profile and implications was done at the department of Otorhinolaryngology, Postgraduate Medical Institute (PGMI), Lady Reading Hospital (LRH), Peshawar-Pakistan. Patients of 6-82 years of age, both genders and nasal polypsis were included. Those patients having intracranial extension of the lesion and refusing for surgery were excluded. Nasal polyps were localized after doing nasal packing. Procedure was performed under local/general anesthesia. Results: There were 38(60%) males and 25(40%) females with male to female ratio of 1.5:1 and with an average age of 34 years. The duration of symptoms ranged from 2 months – 14 years. The main clinical presentations were nasal obstruction 95%, nasal discharge 81%, sneezing 59% and observed nasal polyps 78%. Polyps from ethmoidal region constituted 88% while from lateral nasal wall 12%. Treatment was a combination of surgery and medical therapy with topical corticosteroids. Eighty-Seven percent (87%) of the cases had surgical treatment. The hospital stay ranged from 1-6 weeks with recurrence rate of 13%. Conclusion: Whatever therapeutic regimen is used nasal polyps stay chronic condition in which the cause remains unknown. They are prone to recurrence and in some cases with embarrassing frequencies.